The role of motivation in the association of dispositional mindfulness with self-learning and academic achievement - Aamer Aldbyani; Aamer Aldbyani; Zaid Alhadoor; Zhang Chuanxia; Zhenwen Sheng (Frontiers in Psychology)
IntroductionPrior research has explored relationships among dispositional mindfulness, motivation, and academic performance, the mechanisms linking these variables remain unclear. This study aims to examine whether dispositional mindfulness predicts self-learning and academic achievement in Yemeni college students, and the potential mediating roles of intrinsic and extrinsic motivation in these associations.MethodTwo hundred and eighty-three Yemeni college students (170 males; 18–26 yrs) completed the Mindful Attention Awareness Scale (MAAS), Personal Learning Scale (PLS), Intrinsic/Extrinsic Motivation Scale, and semester GPAs were obtained from college records.ResultsDispositional mindfulness correlated moderately with self-learning (r = 0.49, p < 0.001) and GPA (r = 0.43, p < 0.001). Intrinsic motivation was associated with dispositional mindfulness (r = 0.41), self-learning (r = 0.42) and GPA (r = 0.50), all p < 0.001. PROCESS mediation (Model 4, 5,000 bootstraps) indicated that intrinsic motivation partially mediated the effect of dispositional mindfulness on self-learning (indirect β = 0.07, SE = 0.02, 95% CI [0.03, 0.10]) and GPA (indirect β = 0.06, SE = 0.02, 95% CI [0.02, 0.09]), accounting for ≈ 28 and 35% of the total effects, respectively. Extrinsic motivation showed small zero-order correlations but did not mediate either outcome.ConclusionHigher dispositional mindfulness predicts stronger intrinsic motivation, which in turn fosters sustained self-learning and higher academic achievement; purely extrinsic motives appear insufficient for long-term gains.